The Role of Cross-Cultural Counseling to Increase Tolerance in Islamic Boarding Schools (Pesantren) - Nur Sya'ban Ratri Dwi Mulyani, Yeni; Endah Rahmawati; Yulianton Ashzar Ibrahim (International Journal of Applied Guidance and Counseling, 2024)
Indonesia is a country full of cultural diversity. The language, food, and customs in each region have their own characteristics. This also happens in the pesantren. Each pesantren environment also has its own characteristics. Each student who comes from a different region brings the culture of each region. This causes social conflict between one another. Tolerance is an important value that presents itself as an individual attitude and contributes to peace and order. Tolerance can prevent conflicts within the group. Schools based on pesantren have a role in developing the character of tolerance to students. A counselor needs to have the ability to be sensitive to cultural differences. There needs to be an understanding of the cultural diversity that exists in a school based on pesantren. With an understanding of cultural differences, counselors can understand cultural biases that occur between one student and another. The cultural bias that causes conflict in the school based on the pesantren environment will also be minimized and can even be an alternative to conflict prevention. Cross-cultural counseling has the function of trying to understand humans thoroughly in their cultural context through an interpretative approach. The psychological function possessed by culture allows a study to understand a person's behavior through the expected social roles, norms, and regulations that apply in their environment. The existence of two-way communication in cross-cultural counseling provides students with an understanding of the values ​​and norms contained in each culture. With cross-cultural counseling, it is hoped that it will be able to minimize cultural bias and create tolerance in a school based on pesantren.